Review: Synthesis of Hyaluronic Acid as Food Supplement and Drugs - Brigitta S Maharani; Intan Yustia; Sheren Hana Elia; Gabriela Chelvina S. Girsang; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (Media Pendidikan Gizi dan Kuliner, 2021)
Hyaluronic acid (HA), as a food supplement and drug, is a glycosaminoglycan which is a linear polysaccharide formed from covalently bonded disaccharide units. HA is a polysaccharide formed from repeating units of a disaccharide composed of N-acetyl-D-glucosamine (GalNAc) and D-glucuronic acid (GlcA) with a high molecular weight of between 105 and 108 Da, which are linked alternately by glycosidic bonds (1→ 3) and link(1→4). This structure allows hyaluronic acid to retain large amounts of water and its pseudoplastic fluid properties make hyaluronic acid widely used in the pharmaceutical and cosmetic industries. Sources of hyaluronic acid material can be found from various types of bacteria, land, or marine animals. The purpose of this paper is to present various reviews of hyaluronic acid synthesis methods and determine which method is the most efficient one to do. This review paper contains several research papers from 1934 to 2019 which discuss several methods of hyaluronic acid synthesis including extraction, separation, purification, fermentation, and isolation. Comparison of results shows that the best methods are the repeated batch fermentation and separation because the materials used are quite easy to find and the process is novel yet easy with the high pure products and does not require a long time to obtain HA nanoparticles